Study of the properties of water-air microdispersion of a floatation agent solution - D. Turysbekov (Croatian Metallurgical Society, 2022)
The objective of the study is to investigate the properties of water-air microdispersion of floatation agent solution. The air-water emulsion of flotation agent solution is obtained in the air-water microemulsion generator. Butyl airfloat, foaming agent C-7 and cationic collector butyltriethylenetetramine B-TETA have been studied as reagents. The factors influencing emulsion stability have been determined. It was found that the temperature increase worsens the stability of microdispersion, the optimal speed of the generator is 6 000 rpm and higher. Floatation agent solutions give stable microdispersions at different solution concentrations. The optimum microdispersion is obtained at a generator speed of 6 000 rpm from 0,5 g/l solution of butyl airfloat, from 50 g/l solution of C-7 and B-TETA. The particle size of the dispersion ranges from 41-59 μm.